Open Access Curriculum Study: Can We Improve the Way Medical Students Learn? - Schardt, Connie; Powers, Anne; von Isenburg, Megan; Thibodeau, Patricia L.; Tuttle, Brandi (2007)
Poster presented at 2007 Medical Library Association (MLA)